1995
DOI: 10.1152/jappl.1995.79.2.411
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in relationship between upper airway resistance and ventilation during sleep onset

Abstract: Sleep-induced hypoventilation is caused partly by inadequate compensation for elevated upper airway resistance (UAR). Some evidence suggests that the effect of UAR on ventilation may vary among individuals. The relationship between minute ventilation (VI) and UAR was examined in 26 healthy young men (average of 10.12 sleep onsets). Variables were analyzed over transitions between wakefulness (defined by alpha electroencephalographic activity) and sleep (theta electroencephalographic activity). Transitions to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 19 publications
4
27
1
Order By: Relevance
“…Transitions from alpha to theta and theta to alpha activity were associated with falls and increases in ventilation, respectively, and the magnitude of the change was a positive function of metabolic drive at the time instant of state change. Kay and the co-workers studied whether the changes in upper airway resistance also occur during the transitions between alpha and theta activity [Kay et al 1994, Kay et al 1995, and concluded that changes in upper airway resistance play an important, albeit not exclusive, role in statedependent changes in ventilation during sleep onset. Hence, although in our study we did not carry out a microstructure analysis of EEG, it is likely that the ventilatory oscillations observed in our patients were at least in part due to fluctuations in state related to sleep onset.…”
Section: Eeg Fluctuations During Periodic Breathingmentioning
confidence: 99%
“…Transitions from alpha to theta and theta to alpha activity were associated with falls and increases in ventilation, respectively, and the magnitude of the change was a positive function of metabolic drive at the time instant of state change. Kay and the co-workers studied whether the changes in upper airway resistance also occur during the transitions between alpha and theta activity [Kay et al 1994, Kay et al 1995, and concluded that changes in upper airway resistance play an important, albeit not exclusive, role in statedependent changes in ventilation during sleep onset. Hence, although in our study we did not carry out a microstructure analysis of EEG, it is likely that the ventilatory oscillations observed in our patients were at least in part due to fluctuations in state related to sleep onset.…”
Section: Eeg Fluctuations During Periodic Breathingmentioning
confidence: 99%
“…This is less useful for diagnostic purposes but has been used for comparing the effects of specific treatment modalities such as mandibular advancement devices 21. Clearly this is a rather crude method and, as there is significant variation in upper airway resistance during sleep even between normal individuals,22 this technique is likely to be limited to within individual comparison.…”
Section: Potential Clinical Uses For Pulse Transit Timementioning
confidence: 99%
“…O'Donoghue and coworkers (4) reported in patients with COPD that a sleep-related hypoventilation was due to increased upper airway resistance, and Ballard and coworkers (5) reported an increase in upper airway resistance moving from wakefulness to sleep, although upper airway resistance was not consistently greater during sleep (see Figure 3 of their article [5]). Moreover, in healthy young adults, a poor correlation was observed between changes in ventilation and upper airway resistance (6). Morrell and coworkers (7) addressed the question directly in tracheotomized subjects, confirming hypoventilation during sleep, thus excluding an obligate contribution from upper airway resistance.…”
mentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR)-based metabolomics of exhaled breath condensate (EBC) recognizes markers separating children with asthma or adults with chronic obstructive pulmonary disease from healthy subjects (3-5) and unstable from stable CF (6). No NMR studies in PCD have been reported, and whether EBC metabolic profiles in PCD differ from CF is unknown.…”
mentioning
confidence: 99%